Alternative variants analysis of single-span mobile ropeways based on self-propelled chassis - Tarichko V.I.; Lagerev I.A. (Научно-технический вестник Брянского государственного университета)
Currently, mobile ropeways are considered as one of the promising types of rapidly deployable transport systems, which are formed with the help of two transport and reloading rope complexes based on autonomous self-propelled multi-purpose chassis combined by a single aerial carrying-traction rope system. The key problem in creating effective mobile ropeways of this type is the choice of their rational design, which allows to obtain the best tactical and technical characteristics and quality indicators as a result of the design. The article presents and analyzes possible alternative variants of single-span mobile ropeways based on mobile transport and reloading rope complexes. Based on the results of the comparative analysis, the most preferred variant was established — a single-span single rope mobile ropeway of the pendulum type with a carrying-traction rope system in the form of a closed carrying-traction rope with two parallel branches. The article considers the typical design of the most preferred variant and describes the principle of its operation, as well as lists the main components and mechanisms of the main technological equipment, which should be part of mobile transport and reloading rope complexes.